Patterns and meanings : using corpora for English language research and teaching - Partington, Alan (Studies in corpus linguistics, 1998)
Patterns and Meanings consists of case studies which make use of corpora and concordance technology. Each case study elaborates a problem area, makes reference to both the descriptive and applied literature thus far, and then suggests ways of exploiting corpus data to shed light on the problem. Language phenomena investigated include word sense, phraseology and syntax, metaphor and creative use, text reference, idiom, and translation. Emphasis is given to information that usually cannot be found in dictionaries, grammars, language textbooks or other resources, but which the study of corpus dat.